Superior biocompatibility and comparable osteoinductive properties: sodium-reduced fluoride-containing bioactive glass belonging to the CaO-MgO-SiO2 system as a promising alternative to 45S5 bioactive glass - Schmitz, Sarah I.; Widholz, Benedikt; Essers, Christopher; Becker, M.; Tulyaganov, D. U.; Moghaddam-Alvandi, Arash; Gonzalo de Juan, I.; Westhauser, Fabian (Bioactive materials, 2020)
Bioactive glasses (BGs) are promising bone substitute materials. However, under certain circumstances BGs such as the well-known 45S5 Bioglass® (composition in wt%: 45.0 SiO2, 24.5 Na2O, 24.5 CaO, 6.0 P2O5) act cytotoxic due to a strong increase in pH caused by a burst release of sodium ions. A potential alternative is a sodium-reduced fluoride-containing BG belonging to the CaO-MgO-SiO2 system, namely BG1d-BG (composition in wt%: 46.1 SiO2, 28.7 CaO, 8.8 MgO, 6.2 P2O5, 5.7 CaF2, 4.5 Na2O), that has already been evaluated in-vitro, in-vivo and in preliminary clinical trials. Before further application, however, BG1d-BG should be compared to the benchmark amongst BGs, the 45S5 Bioglass® composition, to classify its effect on cell viability, proliferation and osteogenic differentiation of human mesenchymal stem cells (MSCs). Therefore, in this study, the biocompatibility and osteogenic potential of both BGs were investigated in an indirect and direct culture setting to assess the effect of the ionic dissolution products and the BGs’ physical presence on the cells. The results indicated an advantage of BG1d-BG over 45S5 Bioglass® regarding cell viability and proliferation. Both BGs induced an earlier onset of osteogenic differentiation and accelerated the expression of late osteoblast marker genes compared to the control group. In conclusion, BG1d-BG is an attractive candidate for further experimental investigation. The basic mechanisms behind the different impact on cell behavior should be assessed in further detail, e.g. by further alteration of the BG compositions.
Gesehen am 01.04.2020